Polo‐like‐kinase 1 is a proviral host factor for hepatitis B virus replication. Issue 6 (6th November 2017) - Diab, Ahmed; Foca, Adrien; Fusil, Floriane; Lahlali, Thomas; Jalaguier, Pascal; Amirache, Fouzia; N'Guyen, Lia; Isorce, Nathalie; Cosset, François‐Loïc; Zoulim, Fabien; Andrisani, Ourania; Durantel, David
Abstract : Chronic hepatitis B virus (HBV) infection is a major risk factor for hepatocellular carcinoma (HCC) and current treatments for chronic hepatitis B and HCC are suboptimal. Herein, we identified cellular serine/threonine Polo‐like‐kinase 1 (PLK1) as a positive effector of HBV replication. The aim of this study was to demonstrate the proviral role of PLK1 in HBV biosynthesis and validate PLK1 inhibition a potential antiviral strategy. To this end, we employed physiologically relevant HBV infection models of primary human hepatocytes (PHHs) and differentiated HepaRG cells in conjunction with pharmacologic PLK1 inhibitors, small interfering RNA (siRNA)‐mediated knockdown, and overexpression of constitutively active PLK1 (PLK1 CA ). In addition, a humanized liver Fah −/− /Rag2 −/− /Il2rg −/− (FRG) mouse model was used to determine the antiviral effect of PLK1 inhibitor BI‐2536 on HBV infection in vivo . Finally, in vitro PLK1 kinase assays and site‐directed mutagenesis were employed to demonstrate that HBV core protein (HBc) is a PLK1 substrate. We demonstrated that HBV infection activated cellular PLK1 in PHHs and differentiated HepaRG cells. PLK1 inhibition by BI‐2536 or siRNA‐mediated knockdown suppressed HBV DNA biosynthesis, whereas overexpression of PLK1 CA increased it, suggesting that the PLK1 effects on viral biosynthesis are specific and that PLK1 is a proviral cellular factor. Significantly, BI‐2536 administration to HBV‐infected humanized liver FRG mice strongly inhibited HBV infection, validating PLK1 as an antiviral target in vivo . The proviral action of PLK1 is associated with the biogenesis of the nucleocapsid, as BI‐2536 leads to its decreased intracellular formation/accumulation. In this respect, our studies identified HBc as a PLK1 substrate in vitro, and mapped PLK1 phosphorylation sites on this protein. Conclusion: PLK1 is a proviral host factor that could be envisaged as a target for combined antiviral and antitumoral strategies against HBV infection and HBV‐mediated carcinogenesis. (Hepatology 2017;66:1750–1765)